Antibiogram and molecular insights into quinolone resistance in Salmonella spp. from food-producing animals in the Philippines - Belotindos, Lawrence P; Magalong, Angel Mae C; Salinas, Marvin Bryan S; Miguel, Joel A; Villanueva, Marvin A; Mingala, Claro N; Nakajima, Chie; Suzuki, Yasuhiko (The Journal of Infection in Developing Countries, 2026)
Introduction: The increasing quinolone resistance in food animals in the Philippines has been documented in previous studies. This study aims to investigate the prevalence and underlying molecular mechanisms responsible for quinolone non-susceptibility in Salmonella isolated from food-producing animals. Methodology: A total of 227 Salmonella isolates were obtained from food-producing animals and their derived food products in the Philippines. These isolates were subjected to antimicrobial susceptibility testing against 17 different agents. Quinolone non-susceptible isolates were screened for mutations in the quinolone resistance-determining region (QRDR) and plasmid-mediated quinolone resistance (PMQR) genes. QRDR- and PMQR-positive isolates were also screened for virulence genes and genotyped using the multilocus sequence typing (MLST) method. Results: Most isolates showed high resistance to tetracycline, ampicillin, streptomycin, sulfamethoxazole-trimethoprim, and nalidixic acid. About 68.3% of the isolates showed resistance to at least one antimicrobial agent, and 44.9% exhibited multidrug resistance. Out of the 74 quinolone non-susceptible isolates, 74.3% carried amino-acid substitutions in the QRDR of GyrA and ParC, 4.1% harbored PMQR genes, and 14.9% had both. High-level resistance was associated with double amino-acid substitutions in GyrA (Ser83Phe + Asp87Tyr) and ParC (Thr57Ser + Ser80Ile), while PMQR-positive isolates displayed variable low resistance. Moreover, 17 unique sequence types (STs) were identified, predominantly S. London ST155, S. Infantis ST32, and S. Anatum ST64. All Salmonella isolates exhibit QRDR mutations and/or PMQR genes that possess virulence factors invA and agfA. Conclusions: The findings highlight the widespread fluoroquinolone-resistant Salmonella in food-producing animals and their products, posing a significant threat to the effective treatment of Salmonella-related food-borne diseases.